The effects of cash in advance on export decision: the case of Vietnam - Doan, Ngoc Thang; Nguyen, Kieu Trang; Mai, Phu Cuong (Journal of International Economics and Management, 2022)
This paper investigates the effect of cash in advance (CIA) on the export decision in Vietnamese firms in the face of financial and institutional constraints. We find that the CIA has a positive relationship with the probability of export in the institutionally constrained firms, and this effect becomes pronounced when those firms are small and medium-sized or also suffer financial constraints. This finding suggests that the CIA does help firms export by mitigating the joint effects of constraints imposed on Vietnamese small and medium-sized enterprises (SMEs).